Part I - Access to UV photocured nanostructures via selective morphological trapping of block copolymer melts. Part II - Morphological phase behavior of poly(RTIL) containing block copolymer melts - Scalfani, Vincent F., author; Bailey, Travis S., advisor; Finke, Richard G., committee member; Henry, Charles S., committee member; Kipper, Matt J., committee member; Prieto, Amy L., committee member (Colorado State University. Libraries, 2012)
A thermally stable photocuring system was developed for high fidelity translation of block copolymer based melt-state morphologies into their equivalent solid analogs. Cationic photoacids were combined with partially epoxidized polyisoprene-b-poly(ethylene oxide) (PI-PEO) block copolymers, forming composite blends that allow for extended thermal processing prior to cure, in addition to precise trapping of selected morphologies, a consequence of the temperature independent UV curing mechanism. The parent PI-PEO block copolymer exhibited multiple melt-state morphologies including crystalline lamellae (Lc), hexagonally packed cylinders (C), bicontinuous gyroid (G), and an isotropic disordered state (Dis). Modification of the PI-PEO backbone with epoxy groups and addition of a UV cationic photoacid acted only to shift transition temperatures quantitatively, leaving the overall morphological behavior completely unmodified. UV irradiation exposure of the composite blends directly in the melt-phase at selected temperatures resulted in permanent trapping of both the cylinder and gyroid morphologies from a single block copolymer sample. The studied photocuring chemistry was extended to produce spherical nanostructured hydrogel networks. Fabricated hydrogel networks are built from a pre-structured lattice of body-centered cubic spheres (SBCC), produced via melt-state self-assembly of blended AB diblock and ABA triblock copolymers. Added ABA triblock serves to produce active tethered junction points between the AB diblock spherical micelles. The integrated thermally stable photocuring chemistry allows for in situ trapping of these spherical domains directly in the melt phase, independent from the required thermal processing necessary to achieve the tethered BCC lattice. Specifically, the hydrogel networks were fabricated from partially epoxidized blends of polybutadiene-b-poly(ethylene oxide) diblock (PB-PEO) and PB-PEO-PB triblock copolymers. UV cured samples of composite copolymer disks containing an added amount of UV activated cationic photoinitiator samples retained the SBCC structure with high fidelity, which serves to pre-structure the hydrogel network prior to swelling. Photocured disks preserved their original shape when swollen in water or organic media, were highly elastic and had excellent mechanical properties. Control experiments with uncured samples immediately dissolved or dispersed when swollen. Simple photopatterning of the cross-linked hydrogel system is also explored. The developed pre-structured hydrogel network was then adapted to incorporate light sensitive anthracene groups into the spherical forming AB diblock copolymer for in situ generation of tethering ABA triblock. Pressed disks of anthracene terminated poly(styrene)-b-poly(ethylene oxide) diblock (PS-PEO-An) were photocoupled with UV 365 nm filtered light directly in the melt-phase, post the necessary thermal self-assembly process. Photocoupled disks swelled in water, were highly elastic, had tunable mechanical properties (based on UV irradiation time), and showed complete preservation of initial shape. Swollen photocoupled disks were found to exhibit similar properties to pre-blended PS-PEO/PS-PEO-PS hydrogels with slight differences likely resulting from an asymmetric distribution of triblock in the photocoupled gels. The PS-PEO-An based hydrogels are proposed to be possible future candidates for the development of new asymmetric hydrogels because of their simple fabrication and excellent mechanical properties. In part II of this dissertation, a new poly(room temperature ionic liquid) (RTIL) BCP platform was developed based on the sequential, living ring-opening metathesis polymerization (ROMP) of a hydrophobic non-charged dodecyl ester norbornene monomer followed by a cationic imidazolium norbornene ionic liquid (RTIL) monomer. The synthesized BCPs were found to exhibit surfactant behavior in solution and form highly periodic nanoscale melt morphologies. Extensive control experiments with homopolymer blends do not show any surfactant behavior in solution nor microphase separation in the neat melt phase. After an initial study optimizing the synthesis and verifying the block architecture, a series of 16 poly(RTIL)-based BCP samples were synthesized with varying compositions of 0.42-0.96 vol% poly(norbornene dodecyl ester). A phase diagram was developed through a combination of small-angle X-ray scattering and dynamic rheology. Morphologies identified and assigned within the phase space studied include lamellae (Lam), hexagonally packed cylinders (Hex), a coexistence of Hex and Lam domains in place of the gyroid region, spheres on a body-centered cubic lattice (SBCC), and a "liquid like" packing of spheres (LLP). Annealing samples containing a coexistence of Lam and Hex domains suggest extremely slow ordering kinetics disposing one of the morphologies. The studied poly(RTIL)-based BCPs containing highly charges species are very strongly segregated (large Chi parameter), resulting in limited if any access to the disordered and gyroid regime. Finally, in Appendix I a supramolecular polymer system comprised of benzene-1,3,5-tricarboxamide (BTA) and 2-ureido-4[1H]-pyrimidinone (UPy) functional hydrogenated polybutadiene was developed that forms two unique and independent nanorods motif assemblies. When the two supramolecular motifs are end-capped to different homopolymers, the motifs self-assemble independent of each other into separate nanorod stacked structures. However, when a telechelic polymer is introduced into the system containing both supramolecular motifs (one on each end), a network is formed between the nanorod assemblies. Without the telechelic polymer, the supramolecular material is a viscous liquid with little mechanical integrity. In contrast, addition of the telechelic polymer acts as a cross-linker and results in a networked material that is highly elastic with excellent mechanical properties.
Access to UV photocured nanostructures via selective morphological trapping of block copolymer melts
Morphological phase behavior of poly(RTIL) containing block copolymer melts
Keywords: copolymer; photocuring; phase behavior; cross-link; morphology; RTIL